PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN KINERJA SOSIAL MEDIA - Utama, Louis; Florensia, Silviana; Charity, Angelina; Darmasaputra, Adrian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Content creation in the field of Marketing is something new and very dynamic with many perspectives and definitions in academic and practitioner circles. However, due to differing perspectives, much of the previous literature has confused rather than explained the meaning of content Marketing. Likewise, young people create a lot of digital content but are less precise in carrying out Marketing regarding the activities they will create. Tarsisius High School in creating content on social media such as Instagram does not seem to be making an approach that is appropriate to digital Marketing but is only displaying information. With the development of information technology and digital Marketing, it is deemed necessary for schools to receive guidance on innovation and creativity in creating content on their social media. Digital Marketing training is the right alternative to achieve the right goals in creating content that is right on target and increasing the number of views so that you can create useful content. The solution for community service activities is the creation of social media accounts including to increase partners' online visibility. This includes training in photography and video editing using tools such as Fotoroom and Canva, as well as optimizing Marketing through social media and integrated Marketing communications strategies. ABSTRAK Pembuatan konten dalam bidang pemasaran merupakan sebuah hal yang baru dan bersifat sangat dinamis dengan banyak persepektf dan definisi di dalam kalangan akademik serta praktisi. Namun, karena adanya perbedaan perspektif, banyak literatur sebelumnya yang membingungkan dan bukannya menjelaskan arti pemasaran konten. Demikian pula halnya dengan kalangan muda, banyak membuat konten digital namun kurang tepat dalam menjalankan pemasaran mengenai kegiatan yang akan dibuat. SMA Tarsisius di dalam membuat konten pada social media seperti dalam instagram terlihat kurang membuat pendekatan yang sesuai dengan pemasaran digital melainkan hanya menampilkan sebuah informasi. Dengan berkembangnya teknologi informasi dan pemasaran digital, pihak sekolah dianggap perlu untuk mendapat pembinaan inovasi dan kreativitas dalam membuat konten pada sosial media yang dimiliki. Pelatihan pemasaran digital merupakan alternatif yang tepat untuk mencapai sasaran yang tepat dalam membuat sebuah konten agar tepat sasaran dan meningkatkan jumlah views sehingga dapat membuat konten bermanfaat. Solusi untuk kegiatan pengabdian masyarakat, adalah pembuatan akun media sosial termasuk untuk meningkatkan visibilitas online mitra. Ini termasuk pelatihan dalam fotografi dan editing video menggunakan alat seperti Fotoroom dan Canva, serta optimalisasi pemasaran melalui media sosial dan strategi komunikasi pemasaran terintegrasi.